2019
DOI: 10.3892/or.2019.7131
|View full text |Cite
|
Sign up to set email alerts
|

Deubiquitinase USP9X regulates the invasion of prostate cancer cells by regulating the ERK pathway and mitochondrial dynamics

Abstract: The ubiquitin-specific protease 9X (USP9X) is a conserved deubiquitinase that has been investigated in several types of human cancer. However, the clinical significance and the biological roles of USP9X in prostate cancer remain unexplored. In the present study, an investigation into the expression and clinical significance of USP9X in prostate cancer revealed that USP9X expression was downregulated in prostate cancer tissues compared with that in healthy tissues. In addition, decreased USP9X expression was as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 46 publications
2
6
0
Order By: Relevance
“…In support of this, our study has uncovered a novel regulatory pathway of Drp1 by deubiquitination and stability involving OTUD6A. In addition, USP9X is known to regulate the invasion of prostate cancer cells by inducing ERK-mediated Drp1 phosphorylation, but not the stability [45], suggesting that deubiquitinase may affect the phosphorylation of Drp1 and mitochondrial dynamics. However, in our study, the Drp1-S616A mutant had no effect on the binding of OTUD6A (Fig.…”
Section: Discussionsupporting
confidence: 71%
“…In support of this, our study has uncovered a novel regulatory pathway of Drp1 by deubiquitination and stability involving OTUD6A. In addition, USP9X is known to regulate the invasion of prostate cancer cells by inducing ERK-mediated Drp1 phosphorylation, but not the stability [45], suggesting that deubiquitinase may affect the phosphorylation of Drp1 and mitochondrial dynamics. However, in our study, the Drp1-S616A mutant had no effect on the binding of OTUD6A (Fig.…”
Section: Discussionsupporting
confidence: 71%
“…To further explore the mechanism of Dex regulating drp1 activation, a software package in vivo GPS (iGPS 1.0) (Wang et al, 2020) was used to predict the site-specific kinase for all phosphorylation-sites of Drp1. The prediction results showed that the extracellular regulated protein kinases1/2 (ERK1/2) could significantly regulate the Ser616 site of Drp1 ( Figure 5F and Table 1), and previous studies (Zhao et al, 2019;Zhang et al, 2019) also reported that ERK1/2 is an essential kinase that regulates Drp1. So the effect of ERK1/2 on Dex regulating (E) The intersections of F-actin and mitochondria of VECs in different groups were calculated by Image J software.…”
Section: Dexmedetomidine Phosphorylates Erk1/2-mediated Mitochondrialsupporting
confidence: 59%
“…However, these strategies fail to reflect the physiological regulation of Drp1 function, which is largely controlled by post-translational modifications, of which the phosphorylation at S600 and S579 have received the most attention. Although several reports have highlighted alterations in Drp1 phosphorylation levels in disease settings (Deus et al, 2020;Kashatus et al, 2015;Zhang et al, 2019), the impact, regulation, and interrelation between Drp1 S579 and S600 are poorly understood.…”
Section: Discussionmentioning
confidence: 99%